Study on Standardization Aspects of IoT - Hanhua Lu; Yuanyuan Shao; Hongbo Sun; Bin Ding (Dianxin kexue, 2014)
Standardization aspects of IoT were discussed. After identified the definition of IoT in China, challenges of IoT were put forward. Somebody considered those challenges mainly came from the lack of standards, according to the definition of IoT, different technologies and standards must be included in IoT. It was pointed out that instead of standardization, abstract methods should be the most effective way to make the inclusion. As an example, the sensor and actuator platform built by NUPT was briefly introduced.